A concept of the differentially driven three wheeled robot - Kelemen, Michal; Colville, Daniel John; Kelemenová, Tatiana; Virgala, Ivan; Miková, L'ubica (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the concept of a differentially driven three wheeled robot. The main task for the robot is to follow the navigation black line on white ground. The robot also contains anti-collision sensors for avoiding obstacles on track. Students learn how to deal with signals from sensors and how to control DC motors. Students work with the controller and develop the locomotion algorithm and can attend a competition.
Keywords: robot; education; wheeled locomotion; sensors; mechatronics